Instagramable backdrop for KAED heritage living lab - Ab Jalil, Nurlelawati; Mohd Asri, Ahmad Hareez Adlan (IIUM Press, 2020)
This research aims to study the backdrop design features of Rumah Kutai, a living Malay heritage lab of Kulliyyah of Architecture and Environmental Design (KAED) for the university project. The objectives of the study are to identify the existing backdrop design elements for the project references and to formulate the appropriate backdrop design that applies to the context. The rapid development of information technology nowadays and the domination of the internet as the medium to the contemporary human activities are the factors in the transformation of this heritage living lab into an instagramable architectural’ place. Methodologically, three case studies were selected based on different purposes; as a signage and landmark of a place, a monument of a place, and a public gathering space. The attributes of the design elements, materials, techniques of installation and colour selection were studied with respect to the contextual issues and requirements.